Laparoscopic Versus Open Resection for Rectal Cancer: A Noninferiority Meta-analysis of Quality of Surgical Resection Outcomes. Issue 5 (May 2019) - Acuna, Sergio A.; Chesney, Tyler R.; Ramjist, Joshua K.; Shah, Prakesh S.; Kennedy, Erin D.; Baxter, Nancy N.
Abstract : Objective: To determine whether laparoscopic surgery is noninferior to open surgery for rectal cancer in terms of quality of surgical resection outcomes. Background: Randomized clinical trials (RCTs) have evaluated the oncologic safety of laparoscopic versus open surgery for rectal cancer with conflicting results. Prior meta-analyses comparing these operative approaches in terms of quality of surgical resection aimed to demonstrate if one approach was superior. However, this method is not appropriate and potentially misleading when noninferiority RCTs are included. Methods: MEDLINE, EMBASE, and Cochrane were searched to identify RCTs comparing these operative approaches. Risk differences (RDs) were pooled using random-effects meta-analyses. One-sided Z tests were used to determine noninferiority. Noninferiority margins (ΔNI ) for circumferential resection margin (CRM), plane of mesorectal excision (PME), distal resection margin (DRM), and a composite outcome ("successful resection") were based on the consensus of 58 worldwide experts. Results: Fourteen RCTs were included. Laparoscopic resection was noninferior compared with open resection for the rate of positive CRM [RD 0.79%, 90% confidence interval (CI) −0.46 to 2.04, ΔNI = 2.33%, P NI = 0.026], incomplete PME (RD 1.16%, 90% CI −0.27 to 2.59, ΔNI = 2.85%, P NI = 0.025), and positive DRM (RD 0.15%, 90% CI −0.58 to 0.87, ΔNI = 1.28%, P NI = 0.005). For the rate of "successful resection" (RD 6.16%, 90% CI 2.30–10.02), the comparison was inconclusive when using the ΔNI generated by experts (ΔNI = 2.71%, P NI = 0.07), although no consensus was achieved for this ΔNI . Conclusions: Laparoscopy was noninferior to open surgery for rectal cancer in terms of individual quality of surgical resection outcomes. These findings are concordant with RCTs demonstrating noninferiority for long-term oncologic outcomes between the 2 approaches. Abstract : Supplemental Digital Content is available in the text